Driver-Pressure-State-Impact-Response (DPSIR) Analysis of Landslide Potential in Punten and Gunungsari Villages, Bumiaji District, Batu City, East Java, Indonesia - Rivandi Pranandita Putra; Vita Ayu Kusuma Dewi; Heni Masruroh; Dyah Arum Perwitasari; Diaz Heksa Bintang Pamungkas (CV. Literasi Indonesia, 2025)
Landslides are a recurring hazard in the highland villages of Punten and Gunungsari, Batu City, where natural fragility intersects with human-induced landscape change. This study applied the Driver–Pressure–State–Impact–Response (DPSIR) framework to analyse the socio-ecological dynamics of landslide risk and inform context-appropriate mitigation. A qualitative descriptive approach was employed from May to July 2025, combining field observations, Focus Group Discussions, and in-depth interviews with 100 residents and village authorities. The DPSIR analysis shows that the main Drivers include steep volcanic slopes, high rainfall, agricultural expansion into former forest areas, tourism-driven land conversion, and weak spatial-planning enforcement. These create Pressures such as deforestation, continuous cultivation of shallow-rooted vegetables, soil degradation, inadequate drainage management, and limited financial capacity for soil conservation. The State of the system is characterised by declining slope stability, reduced vegetation cover, increased runoff and sedimentation, and high dependence on climate-sensitive agriculture. Impacts observed include damage to farmland, houses, and infrastructure, livelihood losses, psychological distress during the rainy season, and unequal recovery among households. Existing Responses comprise early warning systems, vetiver and bamboo planting supported by Perhutani and the Indonesian National Armed Forces, disaster awareness activities, and community mutual aid, yet these remain intermittent, weakly maintained, and lacking long-term coordination. The study highlights the need for more preventive, participatory, and integrated land-use governance, supported by sustained community capacity-building and improved seedling access to strengthen slope rehabilitation efforts.